Microplásticos: A Ameaça Invisível. Uma revisão crítica da ocorrência e dos riscos dos microplásticos em ambientes aquáticos - Bernegozzi, Lauren Gabriele Ribeiro (Universidade Federal de São Carlos, 2025)
Microplastics have been widely recognized as emerging contaminants with the potential to significantly impact both the environment and human health. This behavior is primarily due to their persistence, toxicity, and capacity to adsorb various pollutants. The presence of microplastics (MPs) at different stages of treatment processes indicates that, although these systems represent important barriers, they are not fully efficient in particle removal, contributing to their continued release into the environment. The associated risks encompass physical and chemical impacts on aquatic biota, as well as potential ramifications for public health, given their detection in drinking water and human organisms. This study aimed to conduct an updated literature review on the presence, effects, and mitigation strategies related to microplastics in aquatic environments, with emphasis on water and wastewater treatment systems, as well as to evaluate elementary school students’ perceptions of this issue through an informal pedagogical intervention on the topic. The analysis of the outcomes demonstrated limited prior knowledge among students regarding microplastics, and following the educational intervention using informative didactic materials, a significant increase was observed in the understanding of environmental impacts and the importance of proper plastic waste disposal. In conclusion, addressing microplastic pollution requires a coordinated approach involving advancements in sanitation technologies, the establishment of specific regulations, and the implementation of environmental education strategies aimed at increasing public awareness. Therefore, this study reinforces the need to broaden scientific and political discussions focused on controlling microplastic emissions and promoting sustainable practices that mitigate their dispersion in aquatic environments and the associated risks to human health.
Microplastics: The Invisible Threat. A critical review of the occurrence and risks of microplastics in aquatic environments
Keywords: Educação ambiental; Microplásticos; Recursos hídricos; Saúde pública; Saneamento; Environmental education; Public health; Microplastics; Sanitation; Water resources; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ANALITICA::ANALISE DE TRACOS E QUIMICA AMBIENTAL; 4. Educação de Qualidade